2017
DOI: 10.18632/oncotarget.21040
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 mediated the development of cervival cancer through a novel Sp1/Krox-20 swich

Abstract: Cervical cancer is the second leading cause of mortality among women. Impairment of the base excision repair (BER) pathway is one of the major causes of the initiation and progression of cervical cancer. However, whether the polymorphisms of the BER pathway components (i.e., HOGG1, XRCC1, ADPRT, and APE1) can affect the risk of cervical cancer remains unknown. Herein, we applied a hospital-based case-control study covering two independent cohorts and a subsequent functional assay to determine the roles of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…38,39 In addition, Sp1 has been indicated to play a major role in regulating the transcription of XRCC1. 24 The results of this study further indicate that the blocking of Sp1 activation significantly decreases the expression of XRCC1 and drug resistance development in cancer cells treated with MMC. Combining these results suggests that MAPK and transcription factor Sp1 are important signals to elicit clinical resistance development in cancer cells through upregulating the XRCC1 expression.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…38,39 In addition, Sp1 has been indicated to play a major role in regulating the transcription of XRCC1. 24 The results of this study further indicate that the blocking of Sp1 activation significantly decreases the expression of XRCC1 and drug resistance development in cancer cells treated with MMC. Combining these results suggests that MAPK and transcription factor Sp1 are important signals to elicit clinical resistance development in cancer cells through upregulating the XRCC1 expression.…”
Section: Discussionsupporting
confidence: 59%
“…Sp1 has been indicated to be the major transcription factor for BER enzyme genes. 24 To determine whether Sp1 could be activated in MMC-treated AGS cells, the cells were kept as control or treated with MMC (50 μg/mL) for 1, 2, 4, and 8 hours, and then, Sp1 activity was examined. Treatment of cells with MMC significantly increased the Sp1 activity in a time-dependent manner ( Figure 4A).…”
Section: Increases Sp-1 Transcriptional Activity In Ags Cellsmentioning
confidence: 99%
“…Previous studies have demonstrated that XRCC1 plays a role in regulating cell biological features such as proliferation, migration, invasion, and drug resistance in several human cancer cell lines (Xu et al, 2014;Meng et al, 2017;Li et al, 2018;Mei et al, 2019). However, there is no study reporting the function of XRCC1 in gallbladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…As a BER protein, x-ray repair cross-complementing group 1 (XRCC1), a 70-kDa protein, is encoded by the gene located on chromosome 19q13.2-13.3 (Thompson and West, 2000). XRCC1 functions as a scaffold protein in the BER and its aberrant expression is associated with carcinogenesis of multiply human malignant tumors (Hanssen-Bauer et al, 2012;Meng et al, 2017;Mei et al, 2019). Currently, researches on XRCC1 mainly concentrate on the relationship between gene polymorphism and cancer susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…The main function of XRCC1 is associated with its role in the path of single-strand breaks (SSBs) damage and base excision repair (BER) pathways through the enzymatic stage (Campalans et al 2015;Norjmaa et al 2016). XRCC1 gene polymorphism that occurs in DNA repair genes resulting in decreased DNA repair ability, increased mutation rate and cancer risk such as breast, prostate cancer, cervical cancer, and lung cancer (Moullan et al 2003;Rybicki et al 2004;Ochiai 2015;Yuan et al 2015;Meng et al 2017).…”
Section: Introductionmentioning
confidence: 99%